Efficiency of developed solid state bioreactor ‘FERMSOSTAT’ on cellulolytic and xylanase enzymes production - Lee, C.K.; Darah, I; Ibrahim, C.O. (Penerbit Universiti Kebangsaan Malaysia, 2017)
FERMSOSTAT is a developed laboratory scale solid state fermenter. It is a horizontal stirrer drum bioreactor with about 70 L capacities. The fermenter is made of stainless steel which is anti-corrosive and non-toxic to the process organism. The fermenter is equipped with sets of control systems for temperature, agitation, aeration and also outlets for substrate sampling as well as inlets for inoculation and substrate additions. The uniqueness of this FERMSOSTAT system is its ability to carry out in situ substrate sterilization and extraction of enzymes at the end of SSF process. Moreover, the mixing system provided by FERMSOSTAT can be performed either full or half mixing as well as forward or reverse mixing. Furthermore, the mixing can be programmed to run at certain agitation rate and time interval during the fermentation process to prevent or reduce damage to the fungus mycelia. FERMSOSTAT is a developed SSF bioreactor and not an improvement of any existing one. The performances of FERMSOSTAT have been evaluated. Under optimum solid state fermentation conditions, about 63.4, 397 and 3.21 U/g of CMCase, xylanase and FPase activities were detected, which were higher compared to the tray system.